Meningkatkan Hasil Belajar Siswa Menggunakan Model Problem-Based Learning Pada Materi Transformasi - Alvia Dita; Novianita Achmad; Dewi Rahmawaty Isa (Scimadly Publishing, 2025)
This research aims to enhance students' learning outcomes using the Problem-Based Learning model on the topic of Transformation. This study is a classroom action research conducted collaboratively between researchers and teachers involving 30 students in class IX of Satap Tobongon Public Junior High School in the academic year 2023/2024. The research was conducted in two cycles, each comprising three meetings. Instruments used in this study included teacher activity observation sheets, student activity observation sheets, attitude assessment sheets, skill assessment sheets, and learning outcome tests. Data collection was performed through observations and written tests. The research results indicate that the observed teacher activity, categorized as good and very good, increased from 69.44% to 86.11%. Similarly, the observed student activity, categorized as good and very good, increased from 59.38% to 84.38%. Students' learning outcomes improved in the cognitive domain from 66.67% to 86.67%, in the affective domain from 65.00% to 85.83%, and in the psychomotor domain from 67.50% to 85.00%. Thus, all assessment aspects have achieved the learning success indicators in cycle II through the use of the Problem-Based Learning model.